2003
DOI: 10.1046/j.1523-1755.2003.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy and remodeling in relation to ACE and angiotensinogen genes genotypes in Chinese dialysis patients

Abstract: Polymorphism of the AGT M235T gene but not ACE I/D gene is associated with greater LVMi and relative wall thickness, indicating more concentric LVH, in Chinese peritoneal dialysis patients. Possible synergistic effects between AGT and ACE gene polymorphism require further evaluation in a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 56 publications
1
28
2
3
Order By: Relevance
“…37 A study by Ortlepp and col leagues in 26 family members carrying a single mutation in the MyBPC gene revealed a significant association between the angiotensinogen polymorphism and cardiac hypertrophy. 17 Moreover, studies in Chinese, 65 South Korean 66 and Japanese patients 67 found an association between the CC genotype and cardiac hypertrophy. In con trast, the extent of hypertrophy in 108 unrelated Canadian patients was not influenced by angiotensinogen genotype.…”
Section: Angiotensinogenmentioning
confidence: 97%
“…37 A study by Ortlepp and col leagues in 26 family members carrying a single mutation in the MyBPC gene revealed a significant association between the angiotensinogen polymorphism and cardiac hypertrophy. 17 Moreover, studies in Chinese, 65 South Korean 66 and Japanese patients 67 found an association between the CC genotype and cardiac hypertrophy. In con trast, the extent of hypertrophy in 108 unrelated Canadian patients was not influenced by angiotensinogen genotype.…”
Section: Angiotensinogenmentioning
confidence: 97%
“…Influence of the М235Т polymorphism of the AGT gene on HT was also studied [16][17][18]. A few works study impact of this polymorphism on LVH development [19][20][21]. Our study showed correlation of the М235Т polymorphism of the AGT gene with LVH development in HT patients: the MM genotype was observed in patients with LVH more seldom than in HT patients without it (12% vs 21%, р=0,0187).…”
Section: Clinical and Genetic Factors Of Left Ventricular Hypertrophymentioning
confidence: 55%
“…Полиморфизм М235Т гена AGT также изучался в большей степени в его влиянии на развитие АГ [16][17][18]. Небольшое количество работ посвящено изучению влияния данного полимор-физма на развитие ГЛЖ [19][20][21]. В нашем исследовании обнаружена взаимосвязь развития ГЛЖ у больных АГ и полиморфизма М235Т гена AGT: генотип ММ встречал-ся меньше при ГЛЖ, чем у больных АГ без ГЛЖ (12% про-тив 21%, р=0,0187), а в возрасте до 50 лет -8% про-тив 21% (р=0,018).…”
Section: Clinical and Genetic Factors Of Left Ventricular Hypertrophyunclassified
“…Regarding the AGT M235T polymorphism, although it has been reported to be associated with plasma AGT, hypertension, cardiac hypertrophy and coronary artery disease, 15,22 limited reports have discussed its relationship with arrhythmia. 34 Recently, Raizada et al reported no association of AGT M235T polymorphism with QT parameters among patients with end stage renal disease, based on a cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%